2023
DOI: 10.3390/su15021116
|View full text |Cite
|
Sign up to set email alerts
|

Study on Consumers’ Purchase Intentions for Carbon-Labeled Products

Abstract: The carbon-labeling system is able to quantify the level of greenhouse gas emissions of goods throughout their life cycle, including production, delivery, and consumption. With the proposal of carbon peak and carbon neutrality goals, the carbon-labeling system has an inevitable impact on production by companies and the purchase behavior of consumers. This paper constructs a theoretical model of the influencing mechanism on consumer willingness to purchase carbon-labeled products by utilizing the theory of cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…Classes 4 and 5 belong to this category. Class Overall, gender and education level have no significant influence on consumers' preferences for carbon-labeled Huyou, which is similar to the findings of Duan et al [26]. Notably, older individuals tend to prefer lower-priced Huyou products.…”
Section: Consumer Segmentssupporting
confidence: 83%
See 1 more Smart Citation
“…Classes 4 and 5 belong to this category. Class Overall, gender and education level have no significant influence on consumers' preferences for carbon-labeled Huyou, which is similar to the findings of Duan et al [26]. Notably, older individuals tend to prefer lower-priced Huyou products.…”
Section: Consumer Segmentssupporting
confidence: 83%
“…The consensus is that consumers with high income and education levels are likely to pay a high price for carbon-labeled products [24,25]. However, Duan et al [26] concluded that consumers with different incomes and educational levels do not show significant differences in their willingness to purchase carbon-labeled products. Similarly, Shuai et al [11] and Wong et al [27] found that male consumers in China are more willing to purchase carbon-labeled products and pay a higher premium, whereas Liang et al [28] found that female consumers are more willing to accept low-carbon products.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Many studies focus on the influence of psychological factors on pro-environmental behaviors, while the ways in which external situational factors act on behaviors are not clear [91]. It can be seen through the results of the study that the four external factors are direct, positive, and significant regarding rural households' intentions to invest in BIPV projects, and that all four factors are able to trigger rural households' intentions to invest in BIPV.…”
Section: Discussion Of the Main Findingsmentioning
confidence: 89%
“…Liu et al (2017) offer insights into various factors that influence consumers' readiness to purchase low-carbon products, including an understanding of carbon labeling, acceptance of these labels, dependability, consumer perspectives, confidence in the efficacy of adopting low-carbon consumption, societal pressures, influential social groups, costs, and economic incentives. Duan et al (2023) identify that the positive effect on consumers' inclination to purchase carbon-labeled products can be attributed to functional, emotional, and epistemic values. Factors such as low-carbon product delivery speed, consumers' patience, and degree of pleasure also influence customers' willingness to purchase low-carbon products (Liu et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 98%
“…One notable finding from Zhao et al's (2018) study is that, despite consumers' initial skepticism, a substantial majority express an intention to purchase carbon-labeled products. Duan et al (2023) reveal that consumers are willing to pay extra for products with carbon information labels, even in cases where their comprehension of the system is limited. Furthermore, Liang et al (2020) demonstrate that consumers with high levels of objective knowledge and perceived consumer effectiveness are more inclined to purchase products with carbon labels.…”
Section: Literature Reviewmentioning
confidence: 99%